Superimposed structure in the southern periphery of Abu Gharadig Basin, Egypt: Implication to petroleum system - NOURELDIN, Ahmed Mamdouh; MABROUK, Walid Mohamed; METWALLY, Ahmed Mohsen (Contributions to Geophysics and Geodesy, 2023)
South West Abu-Sennan (SWS) area near the southern periphery of the Abu-Gharadig petroliferous basin in the Egyptian Northern Western Desert is an important hydrocarbon field characterized by being a multi-reservoir with a complex structural architecture. Therefore, in this study, we illustrated the regional structural role that facilitated having Jurassic mature source rocks (Masajid and Khatatba formations) through surgical seismic interpretation and observed the controlling petroleum system of the study area using a set of 20 seismic lines and 4 wells data. The study resulted in having the SWS oil field controlled by a strike-slip movement that occurred during the Upper Cretaceous time accompanying the African Plate movement against the Eurasian Plate superimposing an ENE–WSW strike-slip fault zone in the region and a strong pattern of NW–SE-oriented faults due to numerous phases of extension. The associated structures include horsts, normal fault propagation folds, and strike-slip-related anticlines. The strike-slip tectonics played a major role in forming entrapment for the Jurassic expelled hydrocarbons. The seismic horizons flattening exercise performed on AR/G member and Khoman Formation demonstrated that the main reason for not having hydrocarbon accumulations in the Jurassic levels in the study area is that the trap configuration was ready to accumulate hydrocarbon but after the hydrocarbon generation and migration time. The study concluded that the hydrocarbons migrated along the faults which cut deeply to the source rocks and entrapped in the possible cretaceous reservoirs during the late cretaceous time. The conducted workflow in this study can be utilized to better explore and develop cretaceous reservoirs in the study and neighbouring areas.